2022 UKACC 13th International Conference on Control (CONTROL) 2022
DOI: 10.1109/control55989.2022.9781465
|View full text |Cite
|
Sign up to set email alerts
|

LiDAR-based Obstacle Detection and Avoidance for Autonomous Vehicles using Raspberry Pi 3B

Abstract: Autonomous vehicles are redefining the transport industry -obstacle detection and avoidance are key to their operation. A number of sensor technologies have been developed and trialled. This paper presents the implementation of a Hokuyo URG-04LX Light Detection And Ranging (LiDAR) sensor on an autonomous vehicle developed with a Raspberry Pi 3B microcontroller and demonstrates its effectiveness for object detection and avoidance in varying conditions. The LiDAR sensor was integrated with the Raspberry Pi 3B us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to the study by [14], they implemented obstacle detection by using a 2D Light Detection and Ranging (LiDAR) sensor on an autonomous vehicle with a robot operating system (ROS). They used the data collected by the LiDAR sensor to create a 2D mapping on Rviz and also reacting to the obstacle if the distance reading from the sensor reached a certain threshold.…”
Section: A Methods and Sensor To Perform Obstacle Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study by [14], they implemented obstacle detection by using a 2D Light Detection and Ranging (LiDAR) sensor on an autonomous vehicle with a robot operating system (ROS). They used the data collected by the LiDAR sensor to create a 2D mapping on Rviz and also reacting to the obstacle if the distance reading from the sensor reached a certain threshold.…”
Section: A Methods and Sensor To Perform Obstacle Detectionmentioning
confidence: 99%
“…They used the data collected by the LiDAR sensor to create a 2D mapping on Rviz and also reacting to the obstacle if the distance reading from the sensor reached a certain threshold. Tests were carried out for the LiDAR based obstacle detection to detect objects and moving pedestrians and identified that the LiDAR sensor does not respond well to reflective surfaces as the laser light from the LiDAR sensor may not deflected properly, resulting in varied measurement distance that only obtained an average accuracy of 85.92% from the Lidar sensor and actual distance, which also occurs in the research of [14], that utilised Braitenberg strategy, pedestrian detection shows the LiDAR data with higher fluctuation and performs poorer when compared to the ultrasonic sensor, which is likely due to the use of only single laser model for LiDAR measurements, and robot also cannot avoid transparent objects such as acrylic and polycarbonate bottles. The experiment result of [15] shows that the average accuracy during optimal conditions is 99.1%.…”
Section: A Methods and Sensor To Perform Obstacle Detectionmentioning
confidence: 99%